Multifunctional Hydrogels with Temperature, Ion, and Magnetocaloric Stimuli‐Responsive Performances. Issue 9 (14th March 2016) - Wang, Xiao‐Qiao; Yang, Shengyang; Wang, Cai‐Feng; Chen, Li; Chen, Su
Abstract : In this work, multifunctional hydrogels with vivid color change and shrinking–swelling response to temperature, ion strength, and alternating magnetic field are fabricated via magnetic assembly. The hydrogels show gradual shift colors from yellowish green to green, cyan, blue, purple, and even reddish violet in response to temperature or ion strength. In the response process, the whole color modulation process is fully reversible and transferable along with a relative short response time. Especially, the magnetism and porous structure of the hybrid hydrogel enable it to be a potential carrier for hydrophobic molecules. Taking advantage of the magnetocaloric responsiveness, the dyed oil loaded hydrogel exhibits a controllable release behavior in each reversible shrinking–swelling cycle under an alternating magnetic field. This multi‐responsive hydrogel can hold promise for practical engineering applications, including sensors, displays, and controlled release. Abstract : Multifunctional hydrogel is fabricated through a facile magnetic assembly method. This functional hydrogel exhibits very delicate chromatic evolution and multicolor displays to stimulus of temperature or ion strength, and especially can be further used for controlled release through a magnetocaloric effect.